Antibiotic therapy for subclinical mastitis control of lactating cows - Reis, Sonia Rolim; Silva, Nivaldo Adolfo M. da; Brescia, M. V. (Arquivo Brasileiro de Medicina Veterinária e Zootecnia, 2003)
The efficiency of antibiotic therapy to control subclinical mastitis in lactating cows was evaluated. Eighty three udder quarters with subclinical mastitis from three dairy herds were treated with 250mg of cephalothin by intramammary doses. Group 1 included 16 cows in lactation, 15 to 100 days in milk and group 2 included 23 cows in lactation, 101 to 200 days in milk. Therapeutic success was controlled with bacteriological examinations, somatic cells counts (SCC), California Mastitis Test (CMT) and milk production on days zero, 14, 25 and 40 after treatment. Fourteen cows with 28 infected udder quarters were maintained as a control. Staphylococcus aureus and coagulase-negative Staphylococci were the most prevalent microorganism among bacterial isolates. Other pathogens as Bacillus spp, Corynebacterium bovis, Streptococcus uberis and Escherichia coli were present. Concerning bacteriological healing the intramammary therapy reached a 61.4% elimination rate of pathogenic bacteria at the 14th day post treatment. SCC and CMT reactions were decreased too. However, 40 days post-treatment the differences were not significant (P>0.05). No differences among treated groups before and after intramammary treatment (P>0.05) on milk production were observed. Antibiotic treatment of lactating cows with subclinical mastitis was not efficient for controlling the udder infections.
Antibioticoterapia para controle da mastite subclínica de vacas em lactação
Keywords: Antibiotic Agent; Cefalotin; Antibiotic Therapy; Cell Count; Controlled Study; Cow; Elimination Reaction; Escherichia Coli; Lactation; Mastitis; Microbiological Examination; Microorganism; Milk Production; Nonhuman; Pathogenesis; Prevalence; Somatic Cell; Staphylococcus Aureus; Streptococcus Uberis; Bacteria (microorganisms); Bovinae; Corynebacterium; Corynebacterium Bovis; Escherichia Coli; Staphylococcus; Staphylococcus Aureus; Streptococcus; Streptococcus Uberis